2017
DOI: 10.4103/0976-3147.203829
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in Quality of Life and Cognitive Functions in Long-term Survivors of Glioblastoma

Abstract: Background:The incidence of long-term survival in glioblastoma (GBM), i.e., >3 years, ranges from 3% to 5%. Although extensive research is performed in novel therapies for prolonging survival, there is a scarcity of research focusing on the impact of tumor and treatment on cognitive, psychological, and social status of survivors. This study is an attempt to look into this poorly addressed important issue.Materials and Methods:Nine patients (six adults and three children) with GBM who had survived >3 years were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…Our results suggest that better auditory-verbal operational memory, efficiency of perception, and ability to conceptualise corre-late with lower perceived OHRQoL. This conflicts with earlier results for patients suffering from chronic diseases [53][54] but aligns with results for patients with somatic diseases in older age [see [55][56]. This is all the more interesting because the mean age of the studied population was 35 years, making it difficult to explain in terms of age characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results suggest that better auditory-verbal operational memory, efficiency of perception, and ability to conceptualise corre-late with lower perceived OHRQoL. This conflicts with earlier results for patients suffering from chronic diseases [53][54] but aligns with results for patients with somatic diseases in older age [see [55][56]. This is all the more interesting because the mean age of the studied population was 35 years, making it difficult to explain in terms of age characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…Cognitive studies of long term survivors of brain tumors have included primarily patients with low-grade gliomas, considering their longer survival rates relative to those with high-grade gliomas [29]. However, a recent study [30] reported cognitive impairment across several domains in a small group of glioblastoma patients who survived more than three years. Taphoorn et al [31] studied cognitive outcome in a large cohort of low-grade glioma patients (most 1-22 years post RT), in patients with hematologic cancers, and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, the tolerance of tumour cells to therapy makes some residual lesions regrow, so the outcomes have not been satisfactory (Stupp et al, 2009). Furthermore, it has been found that cognitive impairment is one of the most important clinical symptoms and complications of craniocerebral disease in both patients and animal models with gliomas (Solanki et al, 2017;Wang et al, 2011;Weitzner and Meyers, 1997;Van Dyk and Ganz, 2019). Cognitive function occupies an essential position in predicting the prognosis of glioma patients and may even be the first indicator of tumour recurrence after treatment (Crossen et al, 1994;Janelsins et al, 2011;Vecht et al, 2017;Jacob et al, 2018).…”
Section: Introductionmentioning
confidence: 99%